Penilaian Indeks Risiko Metode Modifikasi Andersen dan Metode Modifikasi ICOLD untuk Bendungan Palasari, Bendungan Gerokgak dan Bendungan Benel - Zakariya Ahmad Aji Pamungkas; Hari Nugroho; Kresno Wikan Sadono (Fakultas Teknik, 2023)
Dams are infrastructure that have potential hazards if they are not monitored and maintained. The potential hazard of a dam can be identified through a risk assessment. Risk assessment can consist of risk analysis and risk evaluation. The Palasari Dam, the Gerokgak Dam and the Benel Dam were built to be used to supply water to the northern part of Bali Island. This study aims to determine the level of risk posed by the three dams. Dam risk assessment in the study used the modified ICOLD method and the Andersen modified method. The results of the risk assessment are the basis for consideration in determining maintenance and repair priorities. The results of the dam risk index assessment study, using the Andersen modification method, Palasari Dams, Gerokgak Dams, and Benel Dams have a